The way things work. Magnets [videorecording (DVD)] - Macaulay, David (Schlessinger Media, 2003)
The Mammoth Islanders discover the power of an invisible force called magnetism when lightning strikes their wire and iron bar "clothes dryer." When an electric current flows through the wire, the current creates a magnetic field around it. The Islanders learn that opposites do attract.